Effect of regular application of fertilizers, manure and lime on soil health and productivity of wheat in an acid Alfisol. (26th November 2019) - Dhiman, Diksha; Sharma, Rajpaul; Sankhyan, Narender Kumar; Sepehya, Swapana; Sharma, Sanjay K.; Kumar, Rameshwar
Abstract: The present study on the long-term effect of fertilizers, farmyard manure and lime on changes in soil properties and wheat productivity was carried out at Himchal Pradesh Agricultural University, Palampur (India). The soil was acidic in reaction and classified taxonomically as Typic Hapludalf . Soil samples, collected from two depths viz., 0–0.15 m and 0.15–0.30 m after the harvesting of wheat (2015–2016) were analyzed for different soil properties. Regular use of optimal dose of chemical fertilizers and farmyard manure influenced bulk density, porosity, water holding capacity, saturated hydraulic conductivity, mean weight diameter, pH, organic carbon, cation exchange capacity, available nitrogen, phosphorus, potassium, sulfur, DTPA extractable iron, zinc, copper and manganese, microbial biomass carbon, microbial biomass nitrogen and dehydrogenase activity of soil significantly. Highest grain yield of wheat (30.34 q ha −1 ) was recorded at 100% NPK + FYM which was at par with 100% NPK + lime (27.89 q ha −1 ). However, imbalanced use of nutrients affected different soil properties and productivity adversely.